Hematoma growth is a determinant of mortality and poor outcome after intracerebral hemorrhage - Davis, Stephen; Broderick, J.; Hennerici, Michael G.; Brun, N. C.; Diringer, M. N.; Mayer, S. A.; Begtrup, K.; Steiner, T. (Neurology, 2006)
BACKGROUND: Although volume of intracerebral hemorrhage (ICH) is a predictor of mortality, it is unknown whether subsequent hematoma growth further increases the risk of death or poor functional outcome. - METHODS: To determine if hematoma growth independently predicts poor outcome, the authors performed an individual meta-analysis of patients with spontaneous ICH who had CT within 3 hours of onset and 24-hour follow-up. Placebo patients were pooled from three trials investigating dosing, safety, and efficacy of rFVIIa (n = 115), and 103 patients from the Cincinnati study (total 218). Other baseline factors included age, gender, blood glucose, blood pressure, Glasgow Coma Score (GCS), intraventricular hemorrhage (IVH), and location. - RESULTS: Overall, 72.9% of patients exhibited some degree of hematoma growth. Percentage hematoma growth (hazard ratio [HR] 1.05 per 10% increase [95% CI: 1.03, 1.08; p < 0.0001]), initial ICH volume (HR 1.01 per mL [95% CI: 1.00, 1.02; p = 0.003]), GCS (HR 0.88 [95% CI: 0.81, 0.96; p = 0.003]), and IVH (HR 2.23 [95% CI: 1.25, 3.98; p = 0.007]) were all associated with increased mortality. Percentage growth (cumulative OR 0.84 [95% CI: 0.75, 0.92; p < 0.0001]), initial ICH volume (cumulative OR 0.94 [95% CI: 0.91, 0.97; p < 0.0001]), GCS (cumulative OR 1.46 [95% CI: 1.21, 1.82; p < 0.0001]), and age (cumulative OR 0.95 [95% CI: 0.92, 0.98; p = 0.0009]) predicted outcome modified Rankin Scale. Gender, location, blood glucose, and blood pressure did not predict outcomes. - CONCLUSIONS: Hematoma growth is an independent determinant of both mortality and functional outcome after intracerebral hemorrhage. Attenuation of growth is an important therapeutic strategy.
Gesehen am 09.05.2022